(untitled) (CAHIERS MAGELLANES-NS, 2024)
This article examines the profound impact of customer behavior on the evolution of digital banking in Chennai, a rapidly growing metropolitan city in India. With the rise of digital banking technologies, traditional banking practices have been significantly transformed. This study explores how various demographic, psychographic, economic, and social factors influence customer adoption and satisfaction with digital banking services in Chennai. It also assesses the challenges faced by both customers and traditional banks in this digital transition. Through a review of current trends, customer feedback, and regulatory frameworks, the article provides insights into the changing banking landscape and offers strategic recommendations for banks to enhance their digital offerings and customer engagement. The findings underscore the need for banks to address security concerns, improve digital literacy, and adapt to evolving customer preferences to remain competitive in the digital age.